Beyond the search: how to land the internship that shapes your career? - Abd. Wahab, Fasuriah; shak, Sapiah; Ahmad @Muhammad, Norizam (Faculty of Accountancy, 2025)
Internships have evolved into more than just short-term roles in professional settings-they now serve as a cornerstone of student development and early career readiness. In today's competitive job market, graduates are not only expected to demonstrate academic knowledge but also practical competencies and adaptability to real-world work environments. Internships provide this crucial experiential link, functioning as a bridge between theoretical learning and full-time employment. As the workforce landscape continues to transform rapidly, internships offer a dynamic entry point for students to test their skills, refine their goals, and build lasting professional identities.